Papers of Mary Elizabeth Calwell - Calwell, Mary Elizabeth; Specht, R. L. (Raymond Louis), 1924-2021. (1992)
MS 8761 comprises Mary Elizabeth Calwell's Master of Theology qualifying essay "Early religious influences on Arthur A. Calwell"; copies of correspondence with the Australian Broadcasting Corporation on the film "Admission impossible"; her paper titled "The Bombay papers: an aspect of the 1955 A.L.P. split" (1994); and Calwell's journal articles "Arthur Calwell and Jewish refugees" published in the Centre news, Jewish Holocaust Centre Inc., vol. 28, no. 3 (Dec. 2006), and "Influences, insights and implications" in The Australasian Catholic record, vol. 84, no. 2 (April 2007). Also included are copies of newspaper articles on Arthur Calwell; a paper on "Difficulties in writing a biography" (2002) and other items; and the order of service for the 160th anniversary of the opening of St Francis' Church, Melbourne, October 2005 (1 box, 1 folder).
The Acc10.071 instalment comprises printouts of two emails from Raymond Specht to Mary Elizabeth Calwell, 16 and 20 January 2010, together with a printout of Specht's paper "American-Australian Scientific Expedition to Arnhem Land: its long-term impact", delivered at the National Museum of Australia's 2009 symposium Barks, Birds & Billabongs: Exploring the Legacy of the 1948 American-Australian Scientific Expedition to Arnhem Land (1 packet).
Manuscript reference no.: MS 8761, MS Acc10.071.
Associated materials: Papers of Arthur Calwell, 1905-1973 MS 4738.
Some photocopies.
Dr Mary Elizabeth Calwell is the daughter of Arthur A. Calwell.
Keywords: Calwell, Mary Elizabeth -- Archives; Calwell, Arthur A. -- 1896-1973.; Calwell, Arthur A. -- 1896-1973 -- Religion; Politicians -- Religious life -- Australia; Australia -- Politics and government -- 1945-1965.